DB Schenker Rail customer tailored logistic solutions in relation to the rail freight market between Europe and Asia - Rajnoch, Jan (2012)
For the centuries, the old Silk routes in hinterland Eurasia were connecting the Eastern and Western empires and served as a channel for exchange of goods and ideas between the two different worlds. Over the past decades, the international trade between Europe and Asia has rapidly increased and reflected more than 10 million TEU transported by container ships annually. As far as the silk, spice and other traditional goods have been gradually replaced by laptops, tablets and car components, the new transport solutions have been tested to meet the altering nature of logistic demands. Nowadays, the company DB Schenker Rail is the European leader in the rail freight market and needs to sustain the leading position. However, DB Schenker Rail attempts to be not only the best choice on European rail, but further with the first pioneer back and forth rail freight activities between Europe and Asia tries to capitalize on the new business opportunities. On that account the company has raised the question: What are the rail freight customer needs today and what he will need tomorrow in relation to the logistic processes between Europe and Asia? As a result, several customer tailored logistic solutions have been described to meet the altering nature of rail freight demands.